EFEK PENGUNGKAPAN ESG, LEVERAGE, UKURAN PERUSAHAAN, PROFITABILITAS, DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Putri Permatasari; Darsono Darsono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure, leverage, firm size, profitability, and ownership structure on firm value in energy sector companies listed on the Indonesia Stock Exchange from 2020-2024. The population in this study consists of energy sector companies listed on the Indonesia Stock Exchange during 2020-2024. The sampling technique used was purposive sampling, resulting in 324 firm-year observations. Multiple linear regression was employed as the method of analysis using SPSS software. Firm value was measured using Tobin’s Q, ESG disclosure was proxied by the lagged Bloomberg ESG score, leverage by Debt to Assets Ratio (DAR), profitability by Return on Assets (ROA), firm size by the natural logarithm of total assets, and ownership structure by institutional ownership.The result of this study indicate that ESG disclosure, leverage, firm size, profitability, and ownership structure simultaneously have a significant effect on firm value. Partially, profitability and leverage have a positive effect on firm value. In contrast, ESG disclosure, leverage, firm size, and institusional ownership have a negative and significant effect on firm value, while firm size has no effect on firm value.